Cysteamine Inhibits Glycine Utilisation and Disrupts Virulence in Pseudomonas aeruginosa - Fraser-Pitt, Douglas J.; Dolan, Stephen K.; Toledo-Aparicio, David; Hunt, Jessica G.; Smith, Daniel W.; Lacy-Roberts, Niamh; Nupe Hewage, Piumi Sara; Stoyanova, Teodora N.; Manson, Erin; McClean, Kevin; Inglis, Neil F.; Mercer, Derry K.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Pseudomonas aeruginosa is a major opportunistic human pathogen which employs a myriad of virulence factors. In people with cystic fibrosis (CF) P. aeruginosa frequently colonises the lungs and becomes a chronic infection that evolves to become less virulent over time, but often adapts to favour persistence in the host with alginate-producing mucoid, slow-growing, and antibiotic resistant phenotypes emerging. Cysteamine is an endogenous aminothiol which has been shown to prevent biofilm formation, reduce phenazine production, and potentiate antibiotic activity against P. aeruginosa, and has been investigated in clinical trials as an adjunct therapy for pulmonary exacerbations of CF. Here we demonstrate (for the first time in a prokaryote) that cysteamine prevents glycine utilisation by P. aeruginosa in common with previously reported activity blocking the glycine cleavage system in human cells. Despite the clear inhibition of glycine metabolism, cysteamine also inhibits hydrogen cyanide (HCN) production by P. aeruginosa, suggesting a direct interference in the regulation of virulence factor synthesis. Cysteamine impaired chemotaxis, lowered pyocyanin, pyoverdine and exopolysaccharide production, and reduced the toxicity of P. aeruginosa secreted factors in a Galleria mellonella infection model. Thus, cysteamine has additional potent anti-virulence properties targeting P. aeruginosa, further supporting its therapeutic potential in CF and other infections.